Challenging MXene-based Nanomaterials and Composite Membranes for Water Treatment - Wang, Ling; Xu, Zehai; Fu, Delong; Zhang, Guoliang (Current Analytical Chemistry, 2021)
Background: The development of new emerging nanomaterials for water treatment has attracted more and more interests recently. MXenes is a generic term for a series of new twodimensional (2D) transition metal carbides and carbonitrides materials which have graphene-like structure. As a new type of 2D lamellar nanomaterial, many researches has focused on the design and synthesis of MXene-based nanomaterials owing to their large number of the inter-layer void with the two-dimensional stacking structure, large specific surface area, rich and adjustable surface functional groups, and strong hydrophilicity. On account of their unique properties, related discussion and potential of 2D MXenes nanomaterials for membrane separation and water treatment applications are provided. Objective: The goal of this paper is to review new emerging 2D MXenes nanomaterials for the fabrication of various composite membranes and related applications for water treatment. Methods: In this review, the design and synthesis of MXene-based composite membranes for water treatment was extensively discussed. Results: Membrane separation technology is an effective approach for solving the water pollution problem due to its low energy consumption, environment-friendly, and easy operation. MXene-based membranes with different molecular sieving behaviors for small organic molecules and ions and corresponding applications in water purification and desalination were discussed. Conclusion: Although composite membranes constructed by 2D MXenes nanomaterials can be prepared to achieve high water flux and satisfactory rejection, most research focused on the exploration of membrane formation with a multi-layered compound or few-layered MXenes. In the near future, the functional properties of the MXene itself should be paid more attention for the development of various novel membranes.
Keywords: 2D MXenes nanomaterials